Risk Entanglement in the Finance-State Nexus: The Case of Systemic and Political Risk - Lange, Markus; von Scheve, Christian (Frontiers in Sociology, 2022)
Crises such as European debt crisis, Brexit, and COVID-19 have challenged established relations between finance and the state in attempts at mitigating a broad range of crises-related risks. We ask whether and how these altered relations in themselves constitute novel uncertainties and risks between the two fields. To better understand these dynamics, we introduce the concept of “risk entanglement” to complement financialization as a key concept presently capturing these relations. Based on qualitative research in the German finance-state nexus, we show how financial and state actors mutually construe each other as risks that need to be managed and mitigated to safeguard their particular, field-specific logics and ends. We focus on systemic risk and political risk as two cases of risk entanglement: whereas systemic risk reflects the threat of a potential financial meltdown to the state, political risk reflects how the state endangers established risk practices in finance.